Successful green tourism in remote cultural community areas - Rumpapak Luekveerawattana (Cogent Social Sciences, 2024)
Green tourism in remote communities is of great importance in developing the local economy. This study explores the factors of successful green tourism in remote cultural community areas. This quantitative- and survey-based research collected data from 400 visitors who visited green tourism routes in Wang Yai Village, Wang Sam Mo District, Udon Thani Province, Thailand. They were selected using the systematic sampling method. Structural equation modeling (SEM) was applied for data analysis. The results revealed that the green attraction and green community directly affect the ‘green heart’ and effective management of green tourism sites. These two factors positively influence both internal and external factors such as the ‘green heart’ of the stakeholder and successful management of green tourism sites. This study confirmed the effect of Green attraction (GA) and Green attraction (GC) on Green heart (GH) and effective management of green tourism sites (EE).